Highly Efficient Aligned Ion-Conducting Network and Interface Chemistries for Depolarized All-Solid-State Lithium Metal Batteries - Mu, Yongbiao; Yu, Shixiang; Chen, Yuzhu; Chu, Youqi; Wu, Buke; Zhang, Qing; Guo, Binbin; Zou, Lingfeng; Zhang, Ruijie; Yu, Fenghua; Han, Meisheng; Lin, Meng; et al. (Nano-Micro Letters, 2024)
Improving the long-term cycling stability and energy density of all-solid-state lithium (Li)-metal batteries (ASSLMBs) at room temperature is a severe challenge because of the notorious solid–solid interfacial contact loss and sluggish ion transport. Solid electrolytes are generally studied as two-dimensional (2D) structures with planar interfaces, showing limited interfacial contact and further resulting in unstable Li/electrolyte and cathode/electrolyte interfaces. Herein, three-dimensional (3D) architecturally designed composite solid electrolytes are developed with independently controlled structural factors using 3D printing processing and post-curing treatment. Multiple-type electrolyte films with vertical-aligned micro-pillar (p-3DSE) and spiral (s-3DSE) structures are rationally designed and developed, which can be employed for both Li metal anode and cathode in terms of accelerating the Li+ transport within electrodes and reinforcing the interfacial adhesion. The printed p-3DSE delivers robust long-term cycle life of up to 2600 cycles and a high critical current density of 1.92 mA cm−2. The optimized electrolyte structure could lead to ASSLMBs with a superior full-cell areal capacity of 2.75 mAh cm−2 (LFP) and 3.92 mAh cm−2 (NCM811). This unique design provides enhancements for both anode and cathode electrodes, thereby alleviating interfacial degradation induced by dendrite growth and contact loss. The approach in this study opens a new design strategy for advanced composite solid polymer electrolytes in ASSLMBs operating under high rates/capacities and room temperature. Highlights: 1 This study introduces an innovative 3D-printed electrolyte with vertically aligned ion transport network, which contains well-dispersed nanoscale Ta-doped Li7La3Zr2O12 in a poly(ethylene glycol) diacrylate matrix. 2 The 3DSE architecture enables efficient ion transport across the Li/electrolyte and electrolyte/cathode interfaces, which allows for increased active material mass loading and enhanced interfacial adhesion. 3 The p-3DSE Li symmetric cell displays an impressive critical current density value of 1.92 mA cm−2 and stable operation for 2600 h at room temperature. Full cells using p-3DSE achieve notable areal capacities.